Developing audio-visual materials to teach vocabulary to young learners - Setiawan, Muhammad Dicky; Firdaus, Rizki ALfajri (Aksara Shofa, 2024)
This study aims to create audio-visual resources to enhance vocabulary learning and comprehension among young English as a Foreign Language (EFL) students, with an emphasis on fruit-related vocabulary. Traditional teaching techniques, such as rote memorization, often fail to engage learners and do not encourage long-term retention. In contrast, audio-visual tools like videos, animations, and interactive features provide a more engaging, dynamic, and multimodal learning experience. Using a Research and Development (R&D) methodology, the research will involve needs analysis, material design, prototyping, classroom testing, and evaluation. The effectiveness of the materials will be measured through pre- and post-tests, surveys, and feedback from both students and teachers. This study aims to improve vocabulary retention and comprehension while examining young learners' views on using audio-visual materials in language learning.